(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
Currently, the world pays great attention to the enrichment of minerals. The main method of beneficiation of many ores is the flotation method - aimed at increasing the concentration of useful components in minerals mined from the bowels. Surfactants are considered widely used and indispensable substances for various industrial processes, including the flotation production of sylvin from mineral ores. It is worth recognizing the limited range of collective reagents, and their technological characteristics do not always meet the growing requirements of the industry